الاتصال التربوي بين الاسرة والمدرسة وعلاقته بالتفوق الدراسي - بن عمار, أشواق; بوترعة, بلال (جامعة الوادي - University of Eloued, 2018)
يعتبر الاتصال من بين المواضيع التي لقيت اهتماما بالغا في جميع المجالات عند كافة المختصين والباحثين في مجال السلوك الإنساني عموما، لأنه يعتبر ضرورة إنسانية واجتماعية وحضارية، فحاجة الأفراد له في مختلف البيئات المحلية والاجتماعية، غير أن الاتصال أصبح أكثر تقيدا من ذي قبل مع تطور المجتمعات والرقي الحضاري والتكنولوجي، والانفجار المعرفي الذي يشهده العالم اليوم فهو يمس جميع مؤسسات المجتمع وتنظيماته المختلفة ويتنوع بتنوع هذه مؤسسات، حيث أصبح ضرورة حتمية داخل هذه المؤسسات خاصة المؤسسات التربوية تحت ما يسمى بالاتصال التربوي ويتمثل هذا الأخير في جل العلاقات المختلفة داخل هذه المؤسسة، بل أصبح يشمل مختلف العلاقات التربوية السائدة بين أفراد المجتمع المدرسي وزائريه من رسميين ومهتمين وأولياء الأمور، وهذا ما تهدف له العملية الاتصالية التربوية المعاصرة اليوم، قصد توثيق الصلة بين الأسرة والمدرسة، مما يزيد من بلوغ الأهداف المرجوة من النتائج التعليمية للتلميذ وتفوقه الدراسي. Abstract: Communication is one of the topics that has received great attention in all fields in all the specialists and researchers in the field of human behavior in general, because it is a humanitarian, social and cultural necessity, the need of individuals in different local and social environments, but communication has become more restrictive than before with the development of societies And the cultural and technological advancement, and the explosion of knowledge that the world is witnessing today, it affects all the institutions of society and its various organizations and varied in the diversity of these institutions, where it became an imperative within these institutions, especially educational institutions under the so-called. The educational connection is the latter in the majority of the different relationships within this institution, but it includes the various educational relations prevailing among the members of the school community and visitors of official and interested parents and parents, and this is what the educational process of contemporary education aims to strengthen the relationship between the family and the school, To achieve the desired objectives of the educational outcomes of the student and his academic superiority.
مقال
Keywords: الاتصال التربوي، الاسرة، المدرسة، التفوق الدراسي، التلميذ; Educational Communication, Family, School, Academic Excellence, Student